Genetic Linkage Mapping of Zebrafish Genes and ESTs - Kelly, Peter D.; Chu, Felicia; Woods, Ian G.; Ngo-Hazelett, Phuong; Cardozo, Timothy; Huang, Hui; Kimm, Frankie; Liao, Lingya; Yan, Yi-Lin; Zhou, Yingyao; Johnson, Steven L.; Abagyan, Ruben; et al. (Genome Research, 2000)
Genetic screens in zebrafish (Danio rerio) have isolated mutations in hundreds of genes essential for vertebrate development, physiology, and behavior. We have constructed a genetic linkage map that will facilitate the identification of candidate genes for these mutations and allow comparisons among the genomes of zebrafish and other vertebrates. On this map, we have localized 771 zebrafish genes and expressed sequence tags (ESTs) by scoring single-stranded conformational polymorphisms (SSCPs) in a meiotic mapping panel. Of these sequences, 642 represent previously unmapped genes and ESTs. The mapping panel was comprised of 42 homozygous diploid individuals produced by heat shock treatment of haploid embryos at the one-cell stage (HS diploids). This “doubled haploid” strategy combines the advantages of mapping in haploid and standard diploid systems, because heat shock diploid individuals have only one allele at each locus and can survive to adulthood, enabling a relatively large quantity of genomic DNA to be prepared from each individual in the mapping panel. To integrate this map with others, we also scored 593 previously mapped simple-sequence length polymorphisms (SSLPs) in the mapping panel. This map will accelerate the molecular analysis of zebrafish mutations and facilitate comparative analysis of vertebrate genomes.[A table of the mapped genes and ESTs is provided online at http://www.genome.org.]